2020
DOI: 10.12968/bjcn.2020.25.sup4.s6
|View full text |Cite
|
Sign up to set email alerts
|

Women in dire need: the far-reaching impact of lipoedema on women's lives

Abstract: Lipoedema, an adipose tissue disorder, is a poorly visible, often unrecognised condition. To foster a greater understanding of the significant and debilitating impacts faced by women living with lipoedema, the charity Lipoedema UK conducted four focus group interviews, the findings of which were published in a series of reports under the umbrella title ‘Women in dire need’. The reports identified the substantial and numerous negative effects of lipoedema on the women's everyday lives, including the patients' e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…These findings extend this research by showing that those of stages 3–4 were significantly more likely to report experiencing difficulties at work and in finding and keeping a job due to lipoedema compared to stages 1–2. Qualitative research with stage 3–4 women with lipoedema found mobility issues are a primary concern, impacting everyday activities and work [ 11 ]. Thus, the higher prevalence of impact on work functioning within stages 3–4 in the current study may reflect the greater prevalence of mobility issues, pain and fatigue found in this group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings extend this research by showing that those of stages 3–4 were significantly more likely to report experiencing difficulties at work and in finding and keeping a job due to lipoedema compared to stages 1–2. Qualitative research with stage 3–4 women with lipoedema found mobility issues are a primary concern, impacting everyday activities and work [ 11 ]. Thus, the higher prevalence of impact on work functioning within stages 3–4 in the current study may reflect the greater prevalence of mobility issues, pain and fatigue found in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoedema has a considerable negative impact on everyday functioning in terms of appearance and mobility. Often painful for individuals, the progressive abnormal distribution of fat leads to deterioration of joints and reduces mobility [ 3 ], impacting the ability to engage in physical activity, and work [ 6 , 11 , 12 ]. Importantly, the physical appearance of lipoedema is distressing and reduces emotional and social functioning [ 8 ].…”
mentioning
confidence: 99%
“…It was first described in the United States in 1940 and is characterized by fat accumulation in the lower regions 5 . There is a characteristic of disproportionality in the affected areas, and the symptoms appear throughout development, along with hormonal changes 6 8 .…”
mentioning
confidence: 99%